Biomineralized Piezoelectrically Active Scaffolds for Inducing Osteogenic Differentiation. Issue 15 (8th February 2023) - Ma, Zequn; Hu, Xiantong; Zhang, Yi; Li, Xiangming; Chen, Bo; An, Qi; Zhao, Yantao; Zhang, Yihe
Abstract: There is an endogenous electric field in living organisms, which plays a vital role in the development and regeneration of bone tissue. Therefore, self‐powered piezoelectric material for bone repair has become hot research in recent years. However, the current piezoelectric materials for tissue regeneration still have the shortcomings of lack of biological activity and three‐dimensional structure. Here, we proposed a three‐dimensional polyurethane foam (PUF) scaffold coated with piezoelectric poly (vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP) and modified by a calcium phosphate (CaP) mineralized coating. The preferred scaffold has an open circuit voltage and short circuit current output of 5 V and 200 nA. Combining the physical and chemical properties of the CaP coating, the piezoelectric signal of PVDF‐HFP and the three‐dimensional structure of PUF, the scaffold exhibits superior promotion of cell osteogenic differentiation and ectopic bone formation in vivo. The mechanism is attributed to an increase in intracellular Ca 2+ levels in response to chemical and piezoelectric stimulation with the material. This research not only paves the way for the application of piezoelectric scaffolds to stimulate osteoblasts differentiation in situ, but also lays the foundation for the clinical treatment of long‐term osteoporosis. Abstract : A bone tissue engineering scaffold was developed. The scaffold was realized by coupling porous poly (vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP) coating and calcium phosphate (CaP) coating. Piezoelectric effects can be produced by low‐intensity ultrasound, the self‐motion of the animal body. Through the coupling of piezoelectric effect and physicochemical properties, the scaffold has good osteoinductive ability.